Simultaneous determination of acetylsalicylic acid and salicylic acid in human plasma by isocratic high‐pressure liquid chromatography with post‐column hydrolysis and fluorescence detection. (23rd November 2012) - Hobl, Eva‐Luise; Jilma, Bernd; Ebner, Josef; Schmid, Rainer W.
ABSTRACT: A selective, sensitive and rapid high‐performance liquid chromatography method with post‐column hydrolysis and fluorescence detection was developed for the simultaneous quantification of acetylsalicylic acid and its metabolite salicylic acid in human plasma. Following the addition of 2‐hydroxy‐3‐methoxybenzoic acid as internal standard and simple protein precipitation with acetonitrile, the analytes were separated on a ProntoSIL 120 C18 ace‐EPS column (150 × 2 mm, 3 µm) protected by a C8 guard column (5 µm). The mobile phase, 10 mm formic acid in water (pH 2.9) and acetonitrile (70:30, v/v), was used at a flow rate of 0.35 mL/min. After on‐line post‐column hydrolysis of acetylsalicylic acid (ASA) to salicylic acid (SA) by addition of alkaline solution, the analytes were measured at 290 nm ( λ ex ) and 400 nm ( λ em ). The method was linear in the concentration ranges between 0.05 and 20 ng/μL for both ASA and SA with a lower limit of quantification of 25 pg/μL for SA and 50 pg/μL for ASA. The limit of detection was 15 pg/μL for SA and 32.5 pg/μL for ASA. The analysis of ASA and SA can be carried out within 8 min; therefore this method is suitable for measuring plasma concentrations of salicylates in clinical routine. Copyright © 2012 John Wiley & Sons, Ltd.